2017
DOI: 10.18632/oncotarget.22902
|View full text |Cite
|
Sign up to set email alerts
|

6-(Methylsulfonyl) hexyl isothiocyanate as potential chemopreventive agent: molecular and cellular profile in leukaemia cell lines

Abstract: Numerous laboratory and epidemiological studies show that the risk of developing several types of cancer can be reduced with the employment of natural substances that act with multiple mechanisms. In this context, an important role is played by the isothiocyanates. Recently, 6-(methylsulfonyl)hexyl isothiocyanate (6-MITC), present in the root of Wasabia Japonica, has stimulated the interest of researchers as a chemopreventive agent. In this particular study we have focused on evaluating 6-MITC’s in vitro cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 46 publications
(43 reference statements)
1
24
1
Order By: Relevance
“…1C). This result is different from that in leukemia cells [35], in which there was no significant change in total protein level of P53 from 24 to 48 h in 6-MSITC-treated cells. On the other hand, treatment with sulforaphane, an analog of 6-MSITC, also increased the expression level of P53 in prostate cancer cells [36] and melanoma cells [37], but not in leukemia cells [38].…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…1C). This result is different from that in leukemia cells [35], in which there was no significant change in total protein level of P53 from 24 to 48 h in 6-MSITC-treated cells. On the other hand, treatment with sulforaphane, an analog of 6-MSITC, also increased the expression level of P53 in prostate cancer cells [36] and melanoma cells [37], but not in leukemia cells [38].…”
Section: Discussioncontrasting
confidence: 96%
“…Additionally, death receptors are expected as targets for cancer therapy, because they have capability of inducing apoptosis in cancer cells independent with P53 . 6‐(Methylsulfinyl)hexyl isothiocyanate has reported to induce extrinsic apoptosis via caspase‐8 but not mitochondrial intrinsic apoptosis in leukemia cell lines . In this study, we demonstrated that 6‐MSITC had potency to induce both intrinsic apoptosis and extrinsic apoptosis, independent of p53 status.…”
Section: Discussionmentioning
confidence: 54%
“…6-MITC has many functions, including neuroprotection [ 18 ], anti-inflammation [ 19 ], anti-pulmonary metastasis [ 1 ], chemoprevention [ 2 , 20 ], and cancer prevention [ 3 , 21 , 22 ]. The mechanisms of 6-MITC inhibit tumor growth through the disruption of mitochondrial function or the inhibition of the NF-κB pathway by abrogating the PI3K/AKT pathway to induce apoptosis [ 22 , 23 ] and sensitizing the anti-tumor agent to augment cell killing [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A naturally-occurring compound, 6-(methylsulfinyl) hexyl isothiocyanate (6-MITC), was isolated from Wasabia japonica (wasabi), a pungent spice widely used in Japanese food. Several biological activities of 6-MITC have been reported, such as anti-inflammatory [17,18], neuroprotective [19,20], anti-cancer [21][22][23], and chemopreventive effects [24,25]. Our previous publication indicated that 6-MITC and its derivatives may have an inhibitory effect against pancreatic cancer cell growth (including cancer stem cells phenotype) [26].…”
Section: Introductionmentioning
confidence: 99%